Influences of hydrogen dilution on the growth of Si-based core–shell nanowires by HWCVD, and their structure and optical properties - Al-Masoodi, A.H.H.; Hamzan, N.; Al-Masoodi, A.H.H.; Rahman, Saadah Abdul; Goh, Boon Tong (Springer, 2016)
Si-based core–shell nanowires were grown on Ni-coated crystal silicon substrates using a hot-wire chemical vapor deposition technique. The NiSi nanoparticles acted as catalysts that facilitated the growth of the core–shell nanowires without any hydrogen dilution as well as that ranging from 20 to 99 %. These nanowires were structured by single-crystalline NiSi cores and amorphous shells with consisting of nanocrystallites embedded within an amorphous matrix. Raman results reveal crystallization of amorphous Si to crystalline Si up to the crystalline volume fraction of 92.3 % for the nanowires grown with hydrogen dilution. An increase in hydrogen dilution enhanced the decomposition rate and the gas-phase reactions for SiC shell formation, while further increases up to 99 % suppressed the growth of the nanowires. Moreover, a phased transition from Si to SiC occurred with increases in hydrogen dilution above 20 %. The nanowires demonstrated superior optical absorption in the visible region, revealing their significant light-trapping ability. This paper discusses the influences of hydrogen dilution on the structure and optical properties of these core–shell nanowires.